Genome-Wide Identification and Analysis of Auxin Response Factor Transcription Factor Gene Family in Populus euphratica - Yunzhu Shi; Zixuan Mu; Xiangyu Meng; Xiang Li; Lingxuan Zou; Xuli Zhu; Wenhao Bo (Plants)
Auxin response factor (ARF) is a plant-specific transcription factor that responds to changes in auxin levels, regulating various biological processes in plants such as flower development, senescence, lateral root formation, stress response, and secondary metabolite accumulation. In this study, we identified the ARF gene family in Populus euphratica Oliv. using bioinformatics analysis, examining their conserved structural domains, gene structure, expression products, and evolutionary relationships. We found that the 34 PeARF genes were unevenly distributed on 19 chromosomes of P. euphratica. All 56 PeARF proteins were hydrophilic and unstable proteins localized in the nucleus, with secondary structures containing α-helices, extended strands, random coils, and β-turns but lacking transmembrane helices (TM-helices) and signal peptides. Evolutionary analysis divided the PeARF proteins into five subfamilies (A–E), with high conservation observed in the order and number of motifs, domains, gene structure, and other characteristics within each subfamily. Expression pattern analysis revealed that 17 PeARF genes were upregulated during cell growth and heterophylly development. This comprehensive analysis provides insights into the molecular mechanisms of ARF genes in P. euphratica growth, development, and stress response, serving as a basis for further studies on the auxin signaling pathway in P. euphratica.